Analisis Makna Denotasi dan Konotasi pada Lirik Lagu yang Berjudul Sorai Karya Nadin Amizah - Laili Dwi Rohmah; Rani Jayanti (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Referring to Abdul Chaer’s semantic theory, this study aims to explain the denotative and connotative meanings contained in the lyrics of the song “Sorai” by Nadin Amizah. This study applies a qualitative descriptive method and uses content analysis techniques to identify words, phrases, and sentences in the lyrics that contain denotative and connotative meanings. The findings of this study indicate that the connotative meaning is more dominant and is manifested through the use of natural symbols and emotional expressions that represent human relationships, the process of healing inner wounds, sincerity, and acceptance of true love. This study found that the lyrics of the song “Sorai” not only function as a way to convey messages literally, but also as a way to express deep feelings. Therefore, by using Abdul Chaer’s theory, song lyrics can reveal layers of meaning and demonstrate the power of language as an emotional and aesthetic medium in musical works.